Pengaruh Kepemimpinan dan Budaya Organisasi Terhadap Kepuasan Kerja (Studi pada Kantor Dukcapil Kabupaten Dompu, Nusa Tenggara Barat) - Agus Fahrin Rifani; Irwan Cahyadi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to understand and analyze the extent to which leadership and organizational culture affect employee job satisfaction at the Population and Civil Registration Office (Dukcapil) of Dompu Regency. The research method used in this study is associative quantitative research, which is used to examine statistical data and test a hypothesis. The data collection technique in this study was conducted using a questionnaire. The data analysis technique used is inferential statistical analysis with a multiple linear regression approach. The results of this study indicate that leadership at the Office of Civil Registration and Vital Statistics has an effect on employee job satisfaction. Based on Table 4.17, the calculated t-value is 3.377, which is greater than the table t-value of 1.693, thus showing that Ha is accepted and it can be said that leadership variables have a significant effect on the job satisfaction variable (Y) (Hypothesis 1 is accepted). Among leadership and organizational culture that have a dominant influence on employee job satisfaction, the leadership variable has a regression coefficient value of 0.571. This means that the leadership applied by leaders in the office is very satisfactory, thereby increasing the employees' job satisfaction.